The Stability and Transactivation Potential of the Mammalian MafA Transcription Factor Are Regulated by Serineí 65 Phosphorylation - Guo, Shuangli (American Society for Biochemistry and Molecular Biology, 2009)
The level of the MafA transcription factor is regulated by a variety of effectors of β cell function, including glucose, fatty acids, and insulin. Here, we show that phosphorylation at Ser(65) of mammalian MafA influences both protein stability and transactivation potential. Replacement of Ser(65) with Glu to mimic phosphorylation produced a protein that was as unstable as the wild type, whereas Asp or Ala mutation blocked degradation. Analysis of MafA chimeric and deletion constructs suggests that protein phosphorylation at Ser(65) alone represents the initial degradation signal, with ubiquitinylation occurring within the C terminus (amino acids 234–359). Although only wild type MafA and S65E were polyubiquitinylated, both S65D and S65E potently stimulated transactivation compared with S65A. Phosphorylation at Ser(14) also enhanced activation, although it had no impact on protein turnover. The mobility of MafA S65A was profoundly affected upon SDS-PAGE, with the S65E and S65D mutants influenced less due to their ability to serve as substrates for glycogen synthase kinase 3, which acts at neighboring N-terminal residues after Ser(65) phosphorylation. Our observations not only illustrate the sensitivity of the cellular transcriptional and degradation machinery to phosphomimetic mutants at Ser(65), but also demonstrate the singular importance of phosphorylation at this amino acid in regulating MafA activity.